Yap Regulates Müller Glia Reprogramming in Damaged Zebrafish Retinas - Lourenço, Raquel; Brandão, Ana S.; Borbinha, Jorge; Gorgulho, Rita; Jacinto, António (Frontiers in Cell and Developmental Biology, 2021)
Vertebrates such as zebrafish have the outstanding ability to fully regenerate their retina upon injury, while mammals, including humans, do not. In zebrafish, upon light-induced injury, photoreceptor regeneration is achieved through reprogramming of Müller glia cells, which proliferate and give rise to a self-renewing population of progenitors that migrate to the lesion site to differentiate into the new photoreceptors. The Hippo pathway effector YAP was recently implicated in the response to damage in the retina, but how this transcription coactivator is integrated in the signaling network regulating Müller glia reprogramming has not yet been explored. Here, we show that Yap is required in Müller glia to engage their response to lesion by regulating their cell cycle re-entry and progenitor cell formation, contributing to the differentiation of new photoreceptors. We propose that this regulation is accomplished through a lin28a-ascl1a-dependent mechanism, bona fide Müller glia-reprogramming factors. Overall, this study presents Yap as a key regulator of zebrafish Müller glia reprogramming and consequently retina regeneration upon injury.